2007
DOI: 10.2223/jped.1638
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in Henoch-Schönlein purpura: a multivariate analysis of initial prognostic factors

Abstract: ResumoObjetivos: Identificar fatores preditivos iniciais de envolvimento renal nas crianças e adolescentes com púrpura de Henoch-Schönlein.Métodos: Por um período de 21 anos, os prontuários de 142 pacientes com diagnóstico de púrpura de Henoch-Schönlein admitidos em nosso Hospital Universitário foram revistos. Os fatores preditivos iniciais avaliados nos primeiros 3 meses incluíram: dados demográficos, manifestações clínicas (púrpura palpável persistente, artrite, dor abdominal, dor abdominal intensa, sangrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 19 publications
7
69
1
13
Order By: Relevance
“…On the basis of previous reports, it remains unclear whether severe abdominal pain, persistent purpura, or corticosteroid treatment is associated with the development of HSP nephritis. Multivariate analysis performed by de Almeida et al found severe abdominal pain to be the only independent variable predicting to HSP nephritis, while their univariate analysis indicated that all of these are associated with renal improvement [8]. In our case, renal manifestation occurred before corticosteroid initiation, and it was accompanied by severe abdominal pain and gastrointestinal bleeding.…”
mentioning
confidence: 40%
“…On the basis of previous reports, it remains unclear whether severe abdominal pain, persistent purpura, or corticosteroid treatment is associated with the development of HSP nephritis. Multivariate analysis performed by de Almeida et al found severe abdominal pain to be the only independent variable predicting to HSP nephritis, while their univariate analysis indicated that all of these are associated with renal improvement [8]. In our case, renal manifestation occurred before corticosteroid initiation, and it was accompanied by severe abdominal pain and gastrointestinal bleeding.…”
mentioning
confidence: 40%
“…Hasil serupa juga didapatkan pada analisis bivariat sebelumnya. 24 Analisis multivariat mendapatkan hasil bermakna pada gejala abdomen berat terhadap kejadian nefritis. Gejala abdomen berat juga meningkatkan risiko terjadinya nefritis 3,7 kali dibanding tanpa gejala abdomen berat.…”
Section: Pembahasanunclassified
“…Additional features including arthritis and abdominal pain were accepted as being consistent with the diagnosis (Kawasaki et al, 2003;Reamy et al, 2009). HSPN was defined by abnormal urinalysis results in HSP patients and categorized as follows: normal levels of proteinuria (proteinuria <0.5 g/L and hematuria ≥5 red blood cells per high-power microscopic field); low-grade proteinuria (<1 g/L and/or hematuria ≥5 red blood cells per highpower microscopic field); and heavy proteinuria (≥1 g/L and/or hematuria ≥5 red blood cells per high-power microscopic field) (Hung et al, 2006;de Almeida et al, 2007). The control group included 204 unrelated healthy people (mean age 6.75 ± 2.36 years) recruited from the medical examination center of our hospital.…”
Section: Subjectsmentioning
confidence: 99%